Comparison of percutaneous microwave ablation and laparoscopic resection in the prognosis of liver cancer - Xu, Juan (Int J Clin Exp Pathol, 2015)
The effect of percutaneous microwave ablation and laparoscopic resection on the prognosis of liver cancer was investigated. Ninety patients with liver cancer treated at our hospital from March 2010 to March 2012 were divided into group A and group B (n=45) by using a random number table, and the surgical conditions and the prognosis were compared. The surgical conditions of patients in group A were significantly better than those in group B (P<0.05). The incidence of complications in group A was 6.67%, which was obviously lower than that of group B (P<0.05). The local recurrence rate of group A was 20.00%, and that of group B was 8.89%, which showed a significant difference (P<0.05). The two groups did not differ significantly in terms of either total recurrence rate (P>0.05) or 1-year, 2-year and 3-year survival (P>0.05). Both percutaneous microwave ablation and laparoscopic resection had a good long-term efficacy in liver cancer. However, percutaneous microwave ablation was superior as it caused less invasiveness, reduced the incidence of complications and improved prognosis of liver cancer.